Rational of Current Practice of Prescribing Statin to Treat Dyslipidaemia as Primary Prevention of Coronary Heart Disease in Elderly People - Manwar, Asif; Henein, Michael Y; Amin, Md Nurul; Mohsin, Khaled (Ibrahim Cardiac Medical Journal, 2011)
Background: The efficacy of statin therapy in preventing both primary and secondary coronary heart diseases in young and middle aged people is well known and well supported by numbers of landmark clinical trials. Literatures addressing reduction of cholesterol level in elderly (septogenarians & octogenarians) as primary prevention strategy for coronary heart diseases are scarce. The elderly population rarely suffer from primary heart attack and as such routine prescribing of statin to treat dyslipidaemia as primary prevention of coronary heart disease is controversial, particularly when there are reports that statin therapy in elderly population causes cancer, haemorrhagic stroke, dementia and so on. The present study was aimed at answering these questions in order to help formulating a separate guideline for statin therapy in elderly. Methods: The present study reviewed literatures of recent and recent past origin. A systematic literature search of MEDLINE, EMBASE, CINAHL, Web of Science, CANCERLIT and the Cochrane Systematic Review Database have been used to identify randomized clinical trials of statin use with the main focus on primary or secondary end point of CHD, acute coronary syndrome (ACS), cardiac death, overall death, stroke and cancer diagnosis or cancer death. To be included in this review, (1) the entire study subjects or a sub-group were of age 55 years or more (2) had a mean (or median) duration of patient follow-up of at least 1 year, (3) enrolled a minimum of 100 patients, and (4) reported data on the incidence of either cancer diagnosis or cancer death in the elderly population. Conclusions: The study concludes that statin therapy in elderly people may not provide additional benefit in the prevention of primary cardiovascular diseases or death due to primary cardiovascular events. Though most of the studies ruled out excess risk of cancer or other noncardiovascular events, their probability cannot be entirely ignored. However, there is report that addition of statin to the existing drug schedule of elderly subjects does not cause drug interaction. Large-scale, randomized trial on truly representative population with long term follow up will provide authentic data to answer the question whether statin therapy in elderly people with dyslipidaemia can prevent primary heart diseases. Key words: Statin; primary prevention; coronary heart disease; dyslipidemia; elderly people. Ibrahim Card Med J 2011; 1(1):45-55